Microwave-hydrothermal synthesis of perovskite bismuth ferrite nanoparticles - Biasotto, G. [UNESP]; Simões, Alexandre Zirpoli [UNESP]; Foschini, C. R. [UNESP]; Zaghete, M. A. [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Hydrothermal microwave method (HTMW) was used to synthesize crystalline bismuth ferrite (BiFeO(3)) nanoparticles (BFO) in the temperature of 180 degrees C with times ranging from 5 min to 1 h. BFO nanoparticles were characterized by means of X-ray analyses, Fr-IR, Raman spectroscopy, TG-DTA and FE-SEM. X-ray diffraction results indicated that longer soaking time was benefit to refraining the formation of any impurity phases and growing BFO crystallites into almost single-phase perovskites. Typical FT-IR spectra for BFO nanoparticles presented well defined bands, indicating a substantial short-range order in the system. TG-DTA analyses confirmed the presence of lattice OH(-) groups, commonly found in materials obtained by HTMW process. Compared with the conventional solid-state reaction process, submicron BFO crystallites with better homogeneity could be produced at the temperature as low as 180 degrees C. These results show that the HTMW synthesis route is rapid, cost effective, and could be used as an alternative to obtain BFO nanoparticles in the temperature of 180 degrees C for 1 h. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Crystal growth; X-ray diffraction; Diffusion